The Impact of Chest Therapy on Symptoms Relief and Pulmonary Function in Chronic Obstructive Pulmonary Disease Exacerbations - Nurrahmah Yusuf; Yuris Hikman Karunia; Irmaini Irmaini; Yunita Arliny; Budi Yanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a global health concern defined by persistent respiratory symptoms and irreversible airflow blockage. Excess mucus production and decreased ciliary function in mucus elimination are two of the most common issues among COPD patients. Chest therapy is a physiotherapy practice that helps to remove mucus in a variety of acute and chronic respiratory illnesses. Objective: The study aims to explore how chest treatment affects symptoms and lung function in patients with COPD exacerbations. Methods: This study employed a one-group pretest-posttest design, selecting a sample of 30 COPD exacerbation patients from dr. Zainoel Abidin Hospital through convenience sampling technique. Chest therapy was administered consecutively over six days. Pulmonary function was assessed with a peak flow meter, while symptom improvement was assessed through the BORG questionnaire, Modified Medical Research Council (mMRC) scale, and COPD Assessment Test (CAT). Data analysis was performed using the paired T-test and Wilcoxon test. Results: Chest therapy increased average peak expiratory flow (PEF) by 6.40 L/min, from 29.20 ± 6.26 L/min to 35.60 ± 7.65 L/min. BORG scale scores were likewise reduced, with the majority shifting from scale 4 (56.7%) to scale 2 (40%), as were mMRC scores, which decreased from a dominant scale 3 (40%) to scale 2 (33.3%). Furthermore, CAT scores shifted from the high category (76.7%) to the moderate category (53.3%). Bivariate tests revealed that chest therapy had a significant effect on rising PEF values (P<0.001), decreasing BORG scale scores (P<0.001), and decreasing CAT scores (P = 0.001), but no significant effect was seen on the mMRC scale (P = 0.564). Conclusions: Chest therapy positively impacts lung function, as shown by increased peak expiratory flow (PEF) values and improved clinical symptoms of COPD exacerbation, as measured by BORG and CAT scale scores.